1977
DOI: 10.1111/j.1398-9995.1977.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyposensitization of Patients With Allergic Rhinitis by Intranasal Administration of Chemically Modified Grass Pollen Allergen

Abstract: Immunotherapy has been used for more than 60 years in patients with allergic rhinitis (21). The mechanism underlying the clinical improvement that is often achieved by such treatment is still unclear. One factor that might contribute to this effect in parenteral hyposensitization is the occurrence of high levels of so-called blocking antibodies (3). These are considered to belong mainly to the immunoglobulin class G (16, 17).A good allergen extract for hyposensitization should stimulate a high production of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…In a preliminary study [3], encourag ing results were obtained in allergic rhinitis due to grass pollen using glutaraldehyde-treated, tyrosine-adsorbed mixed grass pollen allergen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a preliminary study [3], encourag ing results were obtained in allergic rhinitis due to grass pollen using glutaraldehyde-treated, tyrosine-adsorbed mixed grass pollen allergen.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study [3], 5 adult pa tients with rhinitis due to allergy to timothy pollen underwent local intranasal hyposen sitization with a chemically modified mixed grass pollen allergen preparation [14]. 4 of these patients experienced diminished hay fever symptoms during the pollen season.…”
Section: Introductionmentioning
confidence: 99%
“…Since the former types of immunoglobulins may act as protective 'blocking antibodies', immunotherapy logically could be directed towards generating the highest titers of these blocking antibodies at the nasal mucosa. Several investigators have reported success ful intranasal immunotherapy particularly for grass pollinosis [1,2,11,20,21], and the practical advantages of such treatment are obvious. During the spring of 1978 and 1979 vol unteers were screened by questionnaire, ex amination of the nose and chest, and prick testing with a battery of common allergens.…”
mentioning
confidence: 99%
“…Figure 1 shows serum IgG and IgE anti-RW levels in RW-and placebo-treated subjects. IgG antibodies were measured in 1978 by the binding of 125I-AgE to protein A conjugated sepharose 4B particles which had previously been incubated with pa tients' sera [2,4]; in 1979 IgG antibodies were relatively quantitated by the binding of 125I-protein A to RW conjugated sephar ose particles which had been incubated with patients' sera [5]. IgE antibodies were mea sured by RAST both years.…”
mentioning
confidence: 99%
“…One way is to modify the allergen preparations chemically in order to reduce their allergenicity, while retaining immunogenicity. Clinical trials of local IT have been performed with modified extracts (6,12,13). The results are promising and indicate that the principle is correct.…”
mentioning
confidence: 99%